The artistic foundations of nations and citizens art, literature, and the political community - Ward, Ann 1970- (Taylor & Francis, 2021)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- List of contributors -- Acknowledgments -- Introduction: The artistic foundations of nations and citizens: art, literature, and the political community -- References -- Part I: Political foundation, citizen virtue, and nation in visual art -- Chapter 1: The Bayeux Tapestry: Nationalism before nations and globes -- The Tapestry -- The ambiguity I: the middle story of Harold and William -- The ambiguity II: on the borders -- Conclusion -- Notes -- Bibliography -- Chapter 2: Justice, peace, and the common good in Trecento Siena: A political study of Ambrogio Lorenzetti's Ben Comune -- Ambrogio Lorenzetti: the artist as thinker -- The republic of Siena and the rule of the Nine -- Lorenzetti's allegories of war, good government, and peace -- Political interpretations of Lorenzetti's visual rhetoric -- Notes -- Bibliography -- Primary Sources -- Secondary Sources -- Chapter 3: J. M. W. Turner and painting politics: The beauty of Britain -- The snow storm: Hannibal and his army crossing the alps -- Dido Building Carthage -- The decline of the Carthaginian empire -- War. The exile and the Rock Limpet -- The slave ship, or slavers throwing overboard the dead and dying-typhon coming on -- Rain, steam, and speed-the Great Western Railway -- Conclusion -- Notes -- Bibliography -- Part II: Republicanism, statesmanship, and nation-building in the plays of William Shakespeare -- Chapter 4: Eros and ordered consent in A Midsummer Night's Dream -- Theseus and the founding of Athens -- The ancient order and the demands of Eros, ambition, and political participation -- What happens in the forest … -- The tradesmen's story -- Conclusion -- Notes -- Bibliography -- Chapter 5: The stagings and statesmanship of Shakespeare's Henry V -- Prince Harry and Falstaff.